CORRELATION BETWEEN THE USE OF FACEBOOK GROUP AND THE 5TH SEMESTER ENGLISH STUDENTS’ ACADEMIC WRITING IN WRITING III COURSE OF FKIP SRIWIJAYA UNIVERSITY - Gustiningdiah Purwandini; Rita Inderawati; Zainal Abidin Naning (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2015)
Abstract: This study was conducted in order to find out the correlation between the use of Facebook group and the academic writing of 5th semester student of the English Education Study Program, FKIP Unsri, taking Writing III course. It also investigated the aspect of writing the students mostly developed, and the students’ perception toward the use of Facebook group in Writing III course. The population was the 5th semester English students of FKIP Sriwijaya University academic year 2013/2014. They were 27 students from class 5B participating as the sample of this study. To collect the data, documentation and questionnaire were used. The students’ academic writing was analyzed based on the rubric, and the questionnaire was analyzed manually by using percentage analysis. To find out the correlation between the use of Facebook group and the students’ academic writing, correlation analysis was utilized. The results of the study showed that there was no significant correlation between the use of Facebook group and the students’ academic writing since r-obtained was lower than r-table (0.154